2019
DOI: 10.1002/jrs.5672
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen rotational Raman linewidth determination considering nonmonoexponential decoherence behavior

Abstract: The rotational Raman linewidth is a vital empirical parameter in determining temperature and concentration in combustion environments from pure rotational anti‐Stokes Raman spectroscopy (RCARS). The Raman linewidth is regularly determined from the coherence dephasing time constant on a picosecond time scale. Oxy‐fuel combustion processes cannot be studied applying the well‐described nitrogen evaluation but are typically based on oxygen evaluation. Therefore, the dephasing behavior of the rotational Raman coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Based on their work, they were able to achieve good control over the measurement of vibrational bands by CARS microscopy by means of optimized performances in specific spectral bands. Hoelzer et al [ 103 ] used nonmonoexponential decoherence behavior to determine oxygen rotational Raman linewidths. Collisional dephasing time constants were obtained from a coherent beating model function.…”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 99%
“…Based on their work, they were able to achieve good control over the measurement of vibrational bands by CARS microscopy by means of optimized performances in specific spectral bands. Hoelzer et al [ 103 ] used nonmonoexponential decoherence behavior to determine oxygen rotational Raman linewidths. Collisional dephasing time constants were obtained from a coherent beating model function.…”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 99%
“…Therefore, it is not surprising that four papers are related to this area. Hölzer et al determined rotational Raman linewidths of molecular oxygen using picosecond time‐resolved rotational CARS. They found that in contrast to the commonly used nitrogen, the rotational dephasing in oxygen shows distinct quantum beating rendering mono‐exponential fitting functions.…”
mentioning
confidence: 99%